Design of haunches in structural steel joints - Kurejková, Marta; Wald, František (Journal of Civil Engineering and Management, 2017)
The paper presents research in design of haunches in structural steel joints. Experimental results of six specimens of haunches with and without flanges are presented. Three specimens are without flanges and three specimens are supported by additional flanges. Flanges differ in stiffness to observe the increase in haunch resistances and the effect on buckling shapes. The research finite element model (RFEA) is studied by material and geometrical nonlinear finite element analysis with imperfections under the actual stress conditions and validated on the measured experimental data. The validity is demonstrated on the comparison of load-deflection curves, failure modes, stress distributions and yield line patterns. The stability analysis of a joint with a haunch is related to the research into component based finite element models of complex joints. The input and the results of the research finite element model are summarised in a benchmark case of a haunch with a flange. A numerical study illustrates the effect of the flange stiffness on the joint’s resistance. The effect is demonstrated on a simple arrangement with triangular stiffeners and on a beam-to-column joint. The main goal of the research is to verify proposed design procedure for stiffeners in steel joints.